A novel preclinical model of craniospinal irradiation in pediatric diffuse midline glioma demonstrates decreased metastatic disease - Knox, Aaron J.; Van Court, Benjamin; Oweida, Ayman; Barsh, Elinor; DeSisto, John; Flannery, Patrick; Lemma, Rakeb; Chatwin, Hannah; Vibhakar, Rajeev; Dorris, Kathleen; Serkova, Natalie J.; Karam, Sana D.; et al. (Frontiers in Oncology, 2023)
Background: Diffuse midline glioma (DMG) is an aggressive pediatric central nervous system tumor with strong metastatic potential. As localized treatment of the primary tumor improves, metastatic disease is becoming a more important factor in treatment. We hypothesized that we could model craniospinal irradiation (CSI) through a DMG patient-derived xenograft (PDX) model and that CSI would limit metastatic tumor. Methods: We used a BT245 murine orthotopic DMG PDX model for this work. We developed a protocol and specialized platform to deliver craniospinal irradiation (CSI) (4 Gy x2 days) with a pontine boost (4 Gy x2 days) and compared metastatic disease by pathology, bioluminescence, and MRI to mice treated with focal radiation only (4 Gy x4 days) or no radiation. Results: Mice receiving CSI plus boost showed minimal spinal and brain leptomeningeal metastatic disease by bioluminescence, MRI, and pathology compared to mice receiving radiation to the pons only or no radiation. Conclusions: In a DIPG PDX model, CSI+boost minimizes tumor dissemination compared to focal radiation. By expanding effective DMG treatment to the entire neuraxis, CSI has potential as a key component to combination, multimodality treatment for DMG designed to achieve long-term survival.